An integrated numerical system to estimate air quality effects of forest fires - Miranda, Ana Isabel
Forest fires are an important source of various gases and particles emitted into the atmosphere that may affect the air quality on a local and/or larger scale. Currently, there is a growing awareness that smoke from wildland fires exposes individuals and populations to hazardous air pollutants. In order to understand and to simulate forest fire effects on air quality, several issues should be analysed and integrated: fire progression, fire emissions, atmospheric flow, smoke dispersion and chemical reactions. In spite of the available models to simulate smoke dispersion and the existence of some systems already covering the main questions, there still remains a lack of integration concerning fire progression. Photochemical pollution is also not included in these modelling systems. AIRFIRE is a numerical system, developed to estimate the effects of forest fires on air quality, integrating several components of the problem through the inclusion of different modules, namely the mesoscale meteorological model MEMO, the photochemical model MARS, and the Rothermel fire spread model. The system was applied to simulate plume dispersion from a wildfire that occurred in a coastal area, close to Lisbon city, at the end of September 1991. Results, namely the obtained pollutants concentration fields, point to a significant impact on the local air quality. Obtained wind fields and concentration patterns revealed the presence of sea breezes and also the influence of the fire in the atmospheric flow. Estimated carbon monoxide concentration levels were very high, exceeding the recommended hourly limit value of the World Health Organization, and ozone concentration values pointed to photochemical production.